2011
DOI: 10.1021/bi101404n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of DNA within a Nanopore: Arginine−Phosphate Tethering and a Binding/Sliding Mechanism for Translocation

Abstract: Protein nanopores show great potential as low-cost detectors in DNA sequencing devices. To date, research has largely focused on the staphylococcal pore α-hemolysin (αHL). In the present study, we have developed simplified models of the wildtype αHL pore and various mutants, in order to study the translocation dynamics of single-stranded DNA under the influence of an applied electric field. The model nanopores reflect the experimentally measured conductance values in planar lipid bilayers. We show that interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 40 publications
3
52
0
Order By: Relevance
“…To aid in such applications, molecular dynamics (MD) simulations are performed to make predictions of the expected current reduction from channel occlusion by a biomolecule compared to the background current across the open channel (20)(21)(22)(23)(24). However, MD simulations have not demonstrated the ability to accurately reproduce experimental data (i.e., channel ionic current), over relevant timescales even when utilizing multiple force fields (FFs) (20,21,23,25).…”
Section: Introductionmentioning
confidence: 99%
“…To aid in such applications, molecular dynamics (MD) simulations are performed to make predictions of the expected current reduction from channel occlusion by a biomolecule compared to the background current across the open channel (20)(21)(22)(23)(24). However, MD simulations have not demonstrated the ability to accurately reproduce experimental data (i.e., channel ionic current), over relevant timescales even when utilizing multiple force fields (FFs) (20,21,23,25).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, we identified the existence and significance of a phosphate‐lysine interaction. Bond et al have since verified this interaction in a separate study . They performed nucleotide translocation simulations through a simplified αHL pore using an applied transmembrane potential and determined that the phosphate‐lysine interaction plays a major role.…”
Section: Introductionmentioning
confidence: 92%
“…635 Bond et al employed all-atom MD simulations to explore the translocation of short strands of DNA through a simplified model of the α -hemolysin pore comprising the stem of the pore surrounded by a membrane mimetic slab. 99 The study examined the effect of cationic amino acids on the translocation dynamics of DNA. Compared to wild type α -hemolysin, arginine mutations were found to reduce the transport rate of DNA through the pore, as well as the ionic current.…”
Section: Typical Questions Of Interestmentioning
confidence: 99%